2022
DOI: 10.1108/rpj-09-2021-0244
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effects of internal architecture on the mechanical properties and mixed-mode fracture behavior of 3D printed CaCO3/ABS nanocomposite samples

Abstract: Purpose The purpose of this study was to investigate the effects of CaCO3 nanoparticles on the mechanical properties, and mixed-mode fracture behavior of acrylonitrile butadiene styrene 3D printed samples with different internal architectures. Design/methodology/approach The nanocomposite filaments have been fabricated by a melt-blending technique. The standard tensile, compact tension and special fracture test samples, named Arcan specimens, have been printed at constant extrusion parameters and at four dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In composite materials, fiber orientation and density play a key role in determining their mechanical properties (Ahmad et al. , 2022; Seyedzavvar and Boğa, 2023). During the printing process of AM, short fibers respond to shear stress by aligning along the printing direction throughout the newly formed parts, this phenomenon is seen with both polymer (Yunus et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In composite materials, fiber orientation and density play a key role in determining their mechanical properties (Ahmad et al. , 2022; Seyedzavvar and Boğa, 2023). During the printing process of AM, short fibers respond to shear stress by aligning along the printing direction throughout the newly formed parts, this phenomenon is seen with both polymer (Yunus et al.…”
Section: Introductionmentioning
confidence: 99%
“…On another front composite materials have gained ground thanks to their superior properties formed by combing certain proportions. In composite materials, fiber orientation and density play a key role in determining their mechanical properties (Ahmad et al, 2022;Seyedzavvar and Bo ga, 2023). During the printing process of AM, short fibers respond to shear stress by aligning along the printing direction throughout the newly formed parts, this phenomenon is seen with both polymer (Yunus et al, 2016;Kaur et al, 2017) and ceramic (Yunus et al, 2017) matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors stated that the presence of CFs increases the mechanical strength of specimens, provided that the fibers are orientated along the direction of maximum principal stresses under any specific loading condition. Seyedzavvar and Bo ga (2022) investigated the effects of CaCO 3 nanoadditives on fracture resistance of 3D-printed ABS samples under various modes of loading. The authors reported that the effects of nanoadditives on the fracture toughness of fabricated samples depend on the type of PP in FFF process, being higher for the specimens of linear architecture than that of other PPs.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the binder is removed by chemical, thermal or thermochemical treatment, and the fabricated workpiece is subjected to conventional sintering in a vacuum furnace [32]. In [33], Seyedzavvar M. and Bo ga C. demonstrated the successful use of an acrylonitrile-butadiene-styrene binder filled with CaCO 3 nanoparticles as a feedstock for obtaining samples by the method of extrusion additive technologies. The addition of nanoparticles led to a significant increase in the tensile strength of the obtained samples.…”
Section: Introductionmentioning
confidence: 99%